This preview shows pages 1–3. Sign up to view the full content.
This preview has intentionally blurred sections. Sign up to view the full version.
View Full Document
Unformatted text preview: U n i v er s i t a s S a s k a t c h ew a n e n s i s DEO ET PAT RIAE 2001 Doug MacLean Derivatives of Exponentials & Logarithms d dx (e x ) = e x and d dx (a x ) = ( ln a)a x d dx ( ln x) = 1 x and d dx ( log a x ) = 1 ( ln a)x We may get more general formulas by using the Chain Rule: d dx e f(x) = e f(x) f (x) and d dx a f(x) = ( ln a)a f(x) f (x) d dx ( ln f(x)) = f (x) f(x) and d dx ( log a f(x) ) = f (x) ( ln a)f(x) = 1 ln a f (x) f(x) The quantity f (x) f(x) is called the relative rate of change of the function f , and is very important in practical applications. Example 1: Find the derivative of y = e 3 x . Solution: y = e 3 x ( 3 x) = e 3 x 3 = 3 e 3 x Example 2: Find the derivative of y = e x 3 . Solution: y = e x 3 (x 3 ) = e x 3 ( 3 x 2 ) = 3 x 2 e x 3 1 Example 3: Find the derivative of y = 3 x 2 . Solution: y = ( ln3 ) 3 x 2 (x 2 ) = ( ln3 ) 3 x 2 ( 2 x) = ( 2 x ln3 ) 3 x 2 Example 4: Find the derivative of y = ln (x 5 + x 3 + 1 ) ....
View
Full
Document
This note was uploaded on 04/08/2008 for the course MATH 106 taught by Professor Piasick during the Spring '08 term at Bryant.
 Spring '08
 Piasick
 Math, Derivative, Formulas

Click to edit the document details